Dynamics of control in construction project teams - Martin Tuuli; Steve Rowlinson; Tas Yong Koh (2010)
Control is pervasive in construction project environments. The management of projects through various planning and control tools has therefore been described essentially as rebureaucratization which increases control over individuals, teams and organizations through ideologies of efficiency and performativity. Yet certain characteristics of the project setting make it an ideal climate for the empowerment of individuals and teams. The manifestations of control in five construction project management teams involved in two ongoing construction projects in Hong Kong are examined. The interpretive and exploratory focus of the study favoured the use of a qualitative research design and the case study approach in particular. Control is viewed as all devices and systems employed to ensure that acts, behaviours, outcomes and decisions of individuals, teams and organizations are consistent with meeting organizational or project goals, objectives and strategies. The findings indicate that a portfolio of control modes is implemented in project teams comprising both formal (i.e. behaviour- and outcome-based) and informal (i.e. clan- and self-based) control mechanisms which are not necessarily incompatible. While formal control remains the primary control mode, a portfolio of control appears necessary to augment the inadequacies of formal control due to the evolving nature of the project environment.